Gerenciamento de resíduos sólidos domiciliares no município de São Francisco de Sales – MG: um estudo de caso - (:unkn) unknown (Universidade Brasil, 2020)
Technological innovations and economic development have influenced the life cycle of industrialized products, making them obsolete in increasingly short periods of time, increasing the amount of waste discharged into nature inappropriately. This has caused an imbalance in the axes of sustainability: economic, social and environmental. The National Solid Waste Policy (PNRS), Federal Law No. 12,305 / 2010, presents several concepts, principles and guidelines for the management and management of waste, presenting resources to small municipalities in order to assist them in making decisions regarding waste household. Thus, fieldwork was carried out in the municipality of São Francisco de Sales - MG. The objective of this research was to describe and compare the practices adopted by the municipality, in relation to the management of household solid waste in the municipality of São Francisco de SalesMG, with the legislation and technical standards in force. The deductive method of qualitative approach of exploratory nature was used, combining the bibliographic research and the case description. Household solid waste collection was monitored for a period of fourteen months in the years 2018 and 2019, with gravimetry from the quarting process. Through measurements made by the author, the average production of 3,696 kg / day of waste in the municipality was identified. It was found that these wastes have inadequate disposal, ignoring the hierarchy presented by the PNRS, where only tailings could go to final disposal in landfills. It has been proven that the management and management of solid waste in the municipality are not in conformity with the technical standards and current legislation. The survey suggests that the municipality draws up its Integrated Solid Waste Management Plan, adapts the current final waste disposal site and implements a sorting and composting plant.
Keywords: Sustentabilidade ambiental; Recursos naturais; Ambiente urbano; CB